2017
DOI: 10.1016/j.scitotenv.2016.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Integrating new indicators of predictors that shape the public's perception of local extreme temperature in China

Abstract: The public’s risk perception of local extreme heat or cold plays a critical role in community health and prevention under climate change. However, there is limited evidence on such issues in China where extreme weather is occurring more frequently due to climate change. Here, a total of 2500 residents were selected using a three-step sampling method and investigated by a questionnaire in two representative cities. We investigated risk perception of extreme heat in Beijing and extreme cold in Harbin in 2013, ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…17 18 Moreover, the public now has a better perception of the potential risks of extreme temperatures in China, especially those with chronic conditions. 19 Since no relevant studies have been reported in China, it is of great value to assess the association between cold spells and AECOPD hospitalisations to build prevention and adaption strategies suitable to local conditions (eg, climate type, sociodemographic status of residents), which may be different from other regions.…”
Section: Introductionmentioning
confidence: 99%
“…17 18 Moreover, the public now has a better perception of the potential risks of extreme temperatures in China, especially those with chronic conditions. 19 Since no relevant studies have been reported in China, it is of great value to assess the association between cold spells and AECOPD hospitalisations to build prevention and adaption strategies suitable to local conditions (eg, climate type, sociodemographic status of residents), which may be different from other regions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this circumstance, it is recommended to collect and survey personal feelings and perceptions in increased extreme heat and vulnerability parameters of the thermal environment from targeted vulnerable people and regions located by assessment outputs. In situ measurements of personal perceptions and ambient thermal environment during extremely hot days are appropriate complements to medical recordings [119]. Heat vulnerability is not bound to cause diseases and deaths, but the knowledge of individual feelings and perceptions in extreme heat is a precise reflection of biophysical exposure and social sensitivity.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…People with higher risk perception level are more likely to resist unhealthy behaviors and adopt healthy lifestyle habits, which helps to increase their level of self-protection against risks and reduce health threats due to various risks. [19][20][21][22][23]. In this study, two variables, physical sub-health risk perception level and clinical manifestations of physical sub-health, were used to collect data from physical examinees through cross-sectional survey.…”
Section: Sample and Data Collectionmentioning
confidence: 99%